Bach spectacular - Camarata, Willy Brookousky (San José, Costa Rica : London, KCT-INDICA, 1983)
Sumario: Obras de Bach, vocal y orquestal
Keywords: BACH, JOHANN SEBASTIAN, -- 1685-1750; MÚSICA BARROCA; GRABACIONES SONORAS